Marine renewable energy handbook - Multon, Bernard (London : ISTE ; Hoboken, NJ : John Wiley & Sons, 2012)
Marine renewable energy is a significant resource for generating electricity, and if some conversion technologies have already reached a certain level of maturity, others are emerging. The originality of this multidisciplinary book is to offer a broad spectrum of knowledge from academic and industry experts of various origins. It deals with general aspects such as the specificities and constraints of the marine environment, the concepts of hydrodynamics and ocean engineering, as well as the industrial and economic sides necessary for the assembly of projects. It also discusses conversion.
4.6.4. Risks linked to deconstruction4.7. Hazard management for interventions at sea; 4.8. Design and maintenance of electricity-producing installations at sea; 4.9. Policies and organization of maintenance; 4.10. Operational and maintenance activities; 4.10.1. Operation; 4.10.2. Maintenance; 4.11. Estimating maintenance costs; 4.12. Decision-making by the investors; 4.13. Conclusion; 4.14. Bibliography; Chapter 5. Installation of Wind Turbines at Sea; 5.1. Peculiarities of the marine environment; 5.1.1. Influence of the waves; 5.1.2. Scouring.
Includes bibliographical references and index.
Print version record.
Keywords: Ocean energy resources; Renewable energy sources -- France; Ocean energy resources -- France; Renewable energy sources -- France; BUSINESS & ECONOMICS -- Real Estate -- General; Ocean energy resources; Renewable energy sources; France; Electronic books